MAR 2022
DOI: 10.24191/mar.v21i03-11
|View full text |Cite
|
Sign up to set email alerts
|

Ceo Facial Masculinity, Characteristics and Earnings Management

Abstract: The present study aimed to examine whether CEO facial masculinity and CEO characteristics help in predicting earnings management (EM). The analyses were based on a panel data of 260 companies listed in Bursa Malaysia over the period 2009 to 2019 with a final sample of 2860 observations. Panel data analysis with fixed effect model was utilized to estimate the results. The results revealed that using facial width-to-height ratio (fWHR) and testosterone (TESTN) as the proxies for CEO facial masculinity had a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Moreover, the study’s results are consistent with stakeholder theory, which asserts that stakeholder involvement in decision-making processes is positively associated with environmental sustainability (Chen et al , 2022a, 2022b, 2022c). Additionally, many studies have concluded that political stability and the absence of violence have a significant and positive effect on sustainability performance (Elsheikh et al , 2022; Odera et al , 2016). The findings also align with prior research indicating that government effectiveness, policy implementation, environmental protection incentives, innovation support, regulations and the rule of law are all associated with enhanced sustainability performance with Arayssi et al (2020), Behl et al (2021), Braam et al (2016), Chairani and Siregar (2021), Chen et al (2022a, 2022b, 2022c), Deswanto and Siregar (2018) and Pereira da Silva (2022).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Moreover, the study’s results are consistent with stakeholder theory, which asserts that stakeholder involvement in decision-making processes is positively associated with environmental sustainability (Chen et al , 2022a, 2022b, 2022c). Additionally, many studies have concluded that political stability and the absence of violence have a significant and positive effect on sustainability performance (Elsheikh et al , 2022; Odera et al , 2016). The findings also align with prior research indicating that government effectiveness, policy implementation, environmental protection incentives, innovation support, regulations and the rule of law are all associated with enhanced sustainability performance with Arayssi et al (2020), Behl et al (2021), Braam et al (2016), Chairani and Siregar (2021), Chen et al (2022a, 2022b, 2022c), Deswanto and Siregar (2018) and Pereira da Silva (2022).…”
Section: Analysis and Discussionmentioning
confidence: 99%